A educação patrimonial como caminho para o conhecimento da história de Boa Vista do Sul - Silva, Reginaldo Rossetto da (My University, 2019)
This work proposes to discuss concepts related to memory, identity and representation, as well as the possibility of inserting Heritage Education in the teaching of history as a way to invigorate and rethink some pedagogical practices, seeking to innovate in the search for new alternatives of research and studies. The objective of the dissertation is to recount part of the history of Boa Vista do Sul, making use of practices related to the ways indicated by IPHAN to identify possible material and immaterial assets, raising as much data as possible. Finally, to make the community feel part of this history, recognizing itself as an integral part of these events, seeking to bring the community closer to its own historical and cultural dynamics through Heritage Education activities. The methodology of following the guidelines of IPHAN's Heritage Education Booklet, and using the inventory records models of Heritage Education was of great importance, since it was thus possible to systematize and optimize both the time and the information that was obtained orally or through research on personal or public documents. Revisiting and formalizing part of the history of the town, which was told by high school students of Marcelino Champagnat State High School and also by residents of the communities, was a process of collective construction, dynamic and that intends to serve as a basis for other researches that may occur in the future. The need of recognition, awareness and preservation of architectural heritage and immaterial practices, such as blessings, prayers or the manufacture of ointments and teas, were some of the patrimonial assets, among many others that were manifested in the town, listed as objects of study for this dissertation.
Este trabalho propõe discutir conceitos relacionados à memória, à identidade, à representação, bem como a possibilidade de inserir a Educação Patrimonial no ensino da história como forma de dinamizar e repensar algumas práticas pedagógicas, buscando inovar na busca de novas alternativas de pesquisa e estudos. O objetivo da dissertação em recontar parte da história de Boa Vista do Sul, fazendo uso de práticas relacionadas aos caminhos indicados pelo IPHAN para identificar possíveis bens materiais e imateriais, levantando a maior quantidade possível de dados a respeito. Por fim, fazer com que a comunidade se sinta parte desta história, se reconhecendo como parte integrante destes eventos, buscando aproximar a comunidade da sua própria dinâmica histórico-cultural através de atividades de Educação Patrimonial. A metodologia de seguir as orientações da Cartilha de Educação Patrimonial do IPHAN, e utilizando os modelos de fichas de inventários de Educação Patrimonial foi de grande importância, pois assim foi possível sistematizar e otimizar tanto o tempo, como as informações que eram obtidas de maneira oral ou através da pesquisa em documentos pessoais ou públicos. Revisitar e formalizar parte da história do município, que foi contada por educandos de nível médio da Escola Estadual de Ensino Médio Marcelino Champagnat e também por moradores das comunidades, foi um processo de construção coletivo, dinâmico e que tem a pretensão de servir de embasamento para outras pesquisas que poderão ocorrer no futuro. A necessidade de reconhecimento, conscientização e de preservação de patrimônios arquitetônicos e de práticas imateriais, como benzeduras, rezas ou a fabricação de pomadas e chás, foram alguns dos bens patrimoniais, dentre tantos outros que se manifestam no município, elencados como objetos de estudos para esta dissertação.
Keywords: História - Boa Vista do Sul (RS); Memória coletiva - Boa Vista do Sul (RS); Identidade social - Boa Vista do Sul (RS); Educação - Boa Vista do Sul (RS) - História; History - Boa Vista do Sul (Brazil); Collective memory - Boa Vista do Sul (Brazil); Group identity - Boa Vista do Sul (Brazil); Education - - Boa Vista do Sul (Brazil) - History